Engineering Aqueous Fiber Assembly into Silk‐Elastin‐Like Protein Polymers. Issue 14 (3rd May 2014) - Zeng, Like; Jiang, Linan; Teng, Weibing; Cappello, Joseph; Zohar, Yitshak; Wu, Xiaoyi
<x xml:space="preserve">Abstract</x> Self‐assembled peptide/protein nanofibers are valuable 1D building blocks for creating complex structures with designed properties and functions. It is reported that the self‐assembly of silk‐elastin‐like protein polymers into nanofibers or globular aggregates in aqueous solutions can be modulated by tuning the temperature of the protein solutions, the size of the silk blocks, and the charge of the elastin blocks. A core‐sheath model is proposed for nanofiber formation, with the silk blocks in the cores and the hydrated elastin blocks in the sheaths. The folding of the silk blocks into stable cores—affected by the size of the silk blocks and the charge of the elastin blocks—plays a critical role in the assembly of silk‐elastin nanofibers. Furthermore, enhanced hydrophobic interactions between the elastin blocks at elevated temperatures greatly influence the nanoscale features of silk‐elastin nanofibers. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>